Egg production, egg quality, blood lipids, and ovarian related indices in laying hens fed pomegranate by-products - Gharagozloo, A; Kheiri, F; Nasr, J; Faghani, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The present experiment was conducted to investigate effects of pomegranate seed (PS) on egg production variables, egg quality traits, blood biochemical attributes, and ovarian related indices of laying hens. A total of 360 Hy-line laying hens (w-80), at 25 weeks of age were randomly allotted to 5 dietary treatments in a completely randomized design during a ten-week period. Experimental treatments consisted of a basal diet (CTL) or supplementation of 1 g, 2 g, 3 g, and 4 g PS/kg to basal diet. Supplementation of 4 g PS/kg feed increased production rate of laying hens by 2.6% (P<0.05) while the other production variables were not affected by dietary treatments. Dietary inclusion of 3 or 4 g PS/kg tended to increase yolk color by 10.7% compared to layers fed on CTL treatment. The greatest large and small yellow follicles count and ovary weight observed when laying hens received 4 g PS/kg feeds compared to those fed on the other dietary treatments (P<0.05). Blood cholesterol content decreased in response to feeding 4 g/kg PS supplemented diets (P<0.05). Furthermore, blood triacylglycerol concentration decreased in layers fed diets containing 3 or 4 g PS/kg (P<0.05). In conclusion, dietary supplementation of 4 g/kg PS seems suitable to improve egg production rate and decrease blood cholesterol and triacylglycerol contents.